1956
DOI: 10.1136/bmj.2.4999.969
|View full text |Cite
|
Sign up to set email alerts
|

Fluothane: A Non-explosive Volatile Anaesthetic Agent

Abstract: "Fluothane" is a new volatile anaesthetic agent developed and manufactured by Imperial Chemical Industries (Raventos, 1956; Raventos and Suckling, 1956). It is the most promising member of a series of agents with non-flammable and non-explosive properties which are being investigated independently by the Medical Research Council. It is a clear, colourless, heavy liquid with a specific gravity of 1860 (cf. chloroform 1500), a boiling-point of 510 C., and a sweetish odour not unlike that of chloroform. Chemicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

1957
1957
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 3 publications
(1 reference statement)
0
23
0
1
Order By: Relevance
“…For this reason the blood-pressure level throughout these operations was unduly low. Further, as has been reported by Bryce-Smith and O'Brien (1956), pulmonary ventilation was depressed during fluothane anaesthesia, especially if the level was sufficient to allow intra-abdominal surgery. It was therefore considered necessary to assist or control the breathing in a large number of our cases.…”
Section: Muscle Relaxantsmentioning
confidence: 52%
See 2 more Smart Citations
“…For this reason the blood-pressure level throughout these operations was unduly low. Further, as has been reported by Bryce-Smith and O'Brien (1956), pulmonary ventilation was depressed during fluothane anaesthesia, especially if the level was sufficient to allow intra-abdominal surgery. It was therefore considered necessary to assist or control the breathing in a large number of our cases.…”
Section: Muscle Relaxantsmentioning
confidence: 52%
“…The results of clinical trials with fluothane have been reported by Johnstone (1956) and by Bryce-Smith and O'Brien (1956). The Committee has carried out a trial with fluothane in 245 patients undergoing surgical operations in four teaching hospitals.…”
Section: Robertsonmentioning
confidence: 98%
See 1 more Smart Citation
“…83 It is nonflammable and nonexplosive when the vapor is mixed with oxygen. 23 Halothane is metabolized by cleavage of the C-Cl bond and possibly of the C-Br bond by enzymes present in microsomes. The C-F bond is not easily broken and, hence, the major products of metabolism are chloride, bromide, and trifluoroacetic acid.…”
Section: Inhalation Anestheticsmentioning
confidence: 99%
“…E. ECKENHOFF et al (1956)' with the following modifications: (1) A microcatheter technique was used to allow to-and-fro sampling of respired gases without interposing dead space;…”
mentioning
confidence: 99%